TRANSBORDER DATA FLOWS: PROTECTION OF MEDICAL TOURIST PERSONAL DATA IN MALAYSIA AND INDONESIA (Journal of International Studies, 2022)
Medical tourism is popular within the Association of Southeast Asian Nations (ASEAN) region, especially in the Indonesian region. Theeconomic prosperity, closer vicinity as compared to Jakarta, and the quality of medical services provided in the neighbouring countrieslead to medical tourism prospering among the Indonesians. Malaysia is one of the most frequently visited countries by Indonesians asmedical tourists. The growth of medical tourism triggers issues of the adequacy of the Indonesian and Malaysian laws to regulatecross-border medical records. It is the aim of this study to examine the adequacy of the current laws in handling cross-border medical records. This study applied doctrinal legal research methodology, i.e., mainly library-based research, where the main legal materials were from Malaysia and Indonesia. It was found that the need for personal data protection is a necessity since boundaries among jurisdictions are becoming “borderless”. The Malaysian law, although comprehensive, has yet to gazette any country as a “whitelisted country” to allow for cross-border data. The Indonesian law does not regulate crossborder medical records. The risk of personal data leakage has become imminent. The importance of cross-border medical records protection is important to create safe integrated medical records. While Malaysia has enacted a comprehensive legal framework on personal data protection (including medical data), Indonesia needs to enhance its legal framework in protecting the data. Regionally, the legal framework of cross-border personal data between Malaysia and Indonesia should be updated in accordance with the ASEAN Data Management Framework.